Factores psicopedagógicos que inciden en la expresión oral y escrita de los estudiantes de la escuela María Piedad Castillo de Leví del cantón Arenillas, 2014 - 2015. - Amendaño Castillo, Jennifer Marylin (2014)
The preparation of children who are educated in the school of Levi Maria Piedad Castillo , for reading and writing is too traditional , despite the professional knowledge or experience obtained their teaching applied in a repetitive manner and technique in some cases obsolete as a result students lose interest in learning and teaching-learning process is affected greatly, this adds up to a number of factors significantly affecting such as educational psychology factors.